Ukraine : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews economic developments in Ukraine during 1996-99. Output decline continued in 1997 and 1998, especially following the August 1998 crisis in Russia. During this period, Ukraine made substantial progress in reducing inflation, mainly through the implementation of a monetary policy that aimed at keeping the exchange rate broadly stable. However, the fiscal situation remained difficult, despite a sizable adjustment in 1998. Throughout the period, economic policy was influenced by developments in international capital markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet